When will employees accept remote working? The impact of gender and internet skills - Ailun Xiong; Senmao Xia; Qile He; Nisreen Ameen; Ji Yan; Paul Jones (Journal of Innovation & Knowledge (JIK), 2023)
The unprecedented COVID-19 pandemic required millions of people across the world to become remote workers. However, little is known about how to achieve effective remote working for organizations. This study investigates the types of employees that are more suited to accepting remote working by considering two determinants: gender and internet skills. Based on an official data set from China, this study reveals that females are more likely to accept remote working, as are those employees with advanced internet skills. This study further investigates the impacts of perceived benefits on employees' acceptance of remote working. It appears that the preference of females for remote working is attributed to avoiding face-to-face interaction rather than free time planning. This study is among the first to reveal how skill matching matters in order to be successful remote workers. Meanwhile, this study indicates that it is gender-specific psychological differences rather than the division of labor in families that motivate females to accept remote working, an important observation which has been neglected so far. The findings are helpful for employers and employees in the post-pandemic era.
Keywords: M120; M150; 650; Employees; Gender; Internet skills; Psychological acceptance; Remote working